PELATIHAN KEWIRAUSAHAAN BAGI SISWA SMK BLK BANDAR LAMPUNG SEBAGAI UPAYA MENUMBUHKAN JIWA KEWIRAUSAHAAN - Rini Loliyani; Rina Loliyana; Hero Desyantama; Astrid Aprica Isabella (Penerbit Widina, Widina Media Utama, 2023)
The translation of entrepreneurship theory into a practical realm requires sufficient reinforcement to create people who are truly resilient in running entrepreneurship. In this elaboration, it is necessary to motivate and provide real examples to prospective business actors so that they have high motivation to start new businesses and open new jobs as well. The main target in providing this motivation is the young generation who have great potential to start new businesses and develop them in the future so that they have a large multiplayer effect in creating new jobs by exploring the potential for creative ideas from BLK Bandar Lampung Vocational School students. One of the goals of this community service is to foster an entrepreneurial spirit and explore the potential that exists in BLK Bandar Lampung Vocational School students to be more creative and innovative in creating a product. As a result, in general, the Entrepreneurship training as an Effort to Grow an Entrepreneurial Spirit at SMK BLK Bandar Lampung was attended by participants enthusiastically. Based on the results of filling out the pre-test and post-test the results show that after the training provided, 80% of students understand the roles, functions, benefits of entrepreneurship ABSTRAKPenjabaran teori berwirausaha menjadi ranah praktis memerlukan penguatan yang cukup untuk menciptakan insan yang betul-betul tangguh dalam menjalankan wirausaha. Dalam penjabaran tersebut diperlukan pemotivasian dan pemberian contoh yang nyata pada calon pelaku usaha agar mempunyai motivasi yang tinggi untuk memulai usaha baru dan membuka lapangan kerja baru juga. Sasaran utama dalam pemberian motivasi tersebut adalah generasi muda yang mempunyai potensi yang besar untuk memulai usaha baru dan mengembangkanya dimasa depan sehingga mempunyai multiplayer effect yang besar dalam penciptaan lapangan kerjabaru dengan menggali potensi ide kreatif dari siswa/siswi SMK BLK Bandar Lampung. Tujuan dari pengabdian kepada masyarakat ini salah satunya adalah menumbuhkan jiwa kewirausahaan dan menggali potensi yang ada pada siswa/siswi SMK BLK Bandar Lampung agar lebih kreatif dan inovatif dalam menciptakan suatu produk. Hasilnya secara umum pelatihan Kewirausahaan Sebagai Upaya Menumbuhkan Jiwa Kewirausahaan di SMK BLK Bandar Lampung diikuti peserta dengan antusias. Berdasarkan hasil pengisian pre-test dan post-test hasilnya menunjukkan bahwa setelah adanya pelatihan yang diberikan, 80% siswa memahami peran, fungsi, manfaat kewirausahaan.